1970
DOI: 10.1136/ard.29.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid excretion in the relatives of patients with gout.

Abstract: This paper describes a study in which uric acid excretion in patients with gout was compared with that of their close relatives. MethodsThe patients all had a diagnosis of primary gout, i.e. they had a characteristic history of acute episodic arthritis with a serum uric acid level above 6 mg./100 ml. and no evident underlying cause for hyperuricaemia. The investigation was carried out before treatment with uratelowering drugs was started. The nature of the study was explained to them and to as many as possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The FCU has not been examined widely in studies on urate, although it has been used in heritability studies in twins [9] and correlations on the handling of urate in gouty patients and their relatives [34]. A significant association has been found between a low FCU (≤6.6%) and SLC2A9 variants [11], and thus highlights the potential of the FCU in understanding the function of SNPs in other urate transporters.…”
Section: Discussionmentioning
confidence: 99%
“…The FCU has not been examined widely in studies on urate, although it has been used in heritability studies in twins [9] and correlations on the handling of urate in gouty patients and their relatives [34]. A significant association has been found between a low FCU (≤6.6%) and SLC2A9 variants [11], and thus highlights the potential of the FCU in understanding the function of SNPs in other urate transporters.…”
Section: Discussionmentioning
confidence: 99%
“…One further patient had been treated for hypothyroidism, a condition which has been associated with hyperuricaemia,6 though this is contentious.7 8 Two patients had a family history of gout; one had evidence of an impaired glomerular filtration rate, and the other had a normal renal function as seen by a normal concentration of urea in blood. Relatives of patients with gout have significantly higher values of serum urate than controls9 10 and it is possible that these two patients had been hyperuricaemic before the effect of the diuretics was added.…”
Section: Discussionmentioning
confidence: 99%
“…Wolfson et al (1949) found that uric acid clearance was rather higher in healthy women than in men, averaging 12-67 ml/min in women and 10-38 ml/min in men. Scott and Pollard (1970), studying the healthy relatives of gouty patients, made sianilar observations. Mean uric acid clearance in male relatives was 7-7 ml/min and in female relatives 8-9 ml/min, and the ratio of uric acid to creatinine clearance was greater in women than in men.…”
Section: Discussionmentioning
confidence: 99%